The implementation of SETS approach towards students achievement on the solubility material based on KKNI - Christina Sitepu; Ruth Mayasari Simanjuntak (Jurnal Pendidikan Kimia (JPKim), 2021)
The low students’ achievement, lack of variety of teaching methods on Basic Chemistry, lack of students’ engagement on teaching and learning process, misconception of Chemistry is difficult subject, and the changes of curriculum into KKNI on Industrial Revolution 4.0 that demand for the students are on the level 6 on the output based on the government legislation are the problems that need to be done on this study. This study aimed to find out the students’ achievement and response during the learning process on Basic Chemistry-Solubility and Solubility Product-class by using SETS approach based on KKNI. This is a quasi experiemental study through the distance learning. The technique of collecting the data was documentation and research instruments that consist of course outlines (RPS), students’ activity (observation sheet), and students’ work sheets that describe the activity with SETS method, pretest and post test, and the student’s questionnaire. The results showed that the implementation of SETS approach affects the students achievement thus there is enhancement on students achievement for the control and experimental class for 51.92% and the students response on the methods are 88%. The Concluded that there is an effect of Using SETS to improve student achievement and increasing student responses to learning. Keywords: SETS, KKNI, Ksp, student achievement